PEMANFAATAN TUMBUHAN SERAI WANGI (Cymbopogon nardus (L.) RENDLE) SEBAGAI ANTIOKSIDAN ALAMI - Willem Hendrik G; Erwin -; Aman Sentosa Panggabean (JURNAL KIMIA MULAWARMAN, 2013)
The phytochemical test, brine shrimp lethality test and antioxidant activity test on secondary metabolits of serai wangi (Cympogon nardus (L.) Rendle) stalk have been completed. Samples are extracted by masseration method that is concentrated by using rotary evaporator. The methanol hard extract are then fractioned with n-hexan and etil n-hexane and ethyl acetate. Based on secondary metabolits phytochemical test of serai wangi (Cympogon nardus (L.) Rendle) stalk showed that methanol raw ekstract contains flavonoid, fenol and triterpenoid. n-hexane fraction extract contain steroid and ethyl Acetat fraction extract contains flavonoid, fenol and terpenoid. In brine shrimp lethality test, the increase larvae death data was recorded and processed using SAS Probit Analysis to determine the Lethal Concentration 50% (LC50) value. The results of this test showed that the most active fraction is n-hexane fraction with LC50 value of 86,9704 ppm. Based on the antioxidant activity by scavenging activity of DPPH used spectrophotometry was obtained that Inhibition Concentration 50% (IC50) of methanol extract is 67,18 ppm, extract of n-hexane fraction is 1.078,41 ppm, extract of ethyl acetat fraction is 68,96 ppm and vitamin C is 3,05 ppm.Keyword: Cympogon nardus (L.) Rendle, Phytochemical Test, Antioxidant Activity Test, DPPH.